Produk Peace Socio Academy Boardgame Wawuh sebagai Media Pengenalan dan Pencegahan Diskriminasi terhadap Kelompok Minoritas: Studi Deskriptif Uji Bermain pada Anggota Pramuka UIN Sunan Gunung Djati Bandung - Abdul Azis Muharam Mulyadi (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
Discrimination against minority groups still occurs in Indonesia, both in the form of verbal and non-verbal violence. The last discrimination that occurred was the closure of the Ahmadiyah Mosque in Garut, West Java in 2021. According to Foucault, discrimination occurs due to the existence of a power system to regulate knowledge and hegemony in society through the normalization of knowledge which is a tool of power so that discrimination and even intolerance can be justified in society. The Wawuh boardgame is a medium for spreading tolerance and peace through 9 basic human rights, namely; the right to life, the right to receive, the right to work, the right to health, the right to education, the right to facilities, the right to protection, the right to voice, and the right to administration. This study aims to determine the extent of changes in perspective and behavior of tolerance after playing the Wawuh Boardgame. This game is played to members of the Scouts of UIN Sunan Gunung Djati Bandung Batch 39 who have not been exposed to the issue of peace and violence based on minority group discrimination. This research method uses a combined qualitative and quantitative approach because the data collection uses a questionnaire whose results will be described in written form and the researcher can describe with a clear purpose. The results and discussion of this study prove that there is an attitude of tolerance and a change in perspective by 86% as well as increasing information about minority groups against members of the Scouts of UIN Sunan Gunung Djati Bandung Batch 39. The conclusion of this study is that the Wawuh Boardgame is effective in campaigning for peace and can introduce minority groups as well as being able to prevent discrimination at all levels.